Electrolyte Technologies for High Performance Sodium-Ion Capacitors - Meng, Fancheng; Long, Tao; Xu, Bin; Zhao, Yixin; Hu, Zexuan; Zhang, Luxian; Liu, Jiehua (Frontiers in Chemistry, 2020)
Bridging the energy gap between batteries and capacitors, while in principle delivering a supercapacitor-like high power density and long lifespan, sodium-ion capacitors (SIC) have been considered promising energy storage devices that could be commercialized in the near future due to the natural abundance of sodium sources and the performance superiority of SIC devices. Therefore, in the past decade, substantial research efforts have been devoted to their structure and property improvements. With regard to the electrochemical performance of an ion capacitor, except for the electrode, the composition and structure of the electrolytes are also of a great importance. Thus, in this mini review, we present a brief summary of the electrolytes developed recently for high performance SIC, including aqueous, organic, and ionic liquid based electrolytes. The influence factors such as ionic conductivities, electrolyte concentrations, electrochemical stable windows, as well as the cost and safety issues are discussed. Furthermore, the future perspectives and challenges in the science and engineering of new type electrolytes are also outlooked. We hope that this review may be helpful to the energy storage community regarding the electrolytes of advanced SIC system.